The Impact of Marketing Mix 4Ps and Consumer Behavior toward Purchase Decision of Adidas Products - Clara Ang; Hariadi Rusli (iBuss Management, 2018)
In the recent year, there are so many international brands in the apparel and footwear industry which force Adidas to be able to come up with a good marketing strategy. There are a lot of ways in determining the marketing strategy but this research will be focused on understanding the impact of marketing mix 4Ps and consumer behavior toward purchase decision of Adidas products. Consumer behavior is believed to be able to complete marketing mix 4Ps as they are focused on understanding consumers’ perspective.There are 125 samples being used in this research by using simple random sampling as the sampling method. Those samples are analyzed by using binary logistic regression and cross tabulation. From the analysis, the result shows that marketing mix 4Ps are simultaneously influence purchase decision of Adidas products. However, only product, price, and promotion that individually have significant influence toward purchase decision of Adidas products. As for the consumer behavior, each of the factor have correlation with consumers purchase decision of Adidas products. Keyword: Marketing Mix, Consumer Behavior, Purchase Decision